2022
DOI: 10.52711/2231-5691.2022.00050
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Senna alata – A Review

Abstract: Senna alata is one of the species of Senna plant from the family of Fabaceae. It is not only the ornamental plant but also possesses many medicinal activities. Antifungal, antibacterial, laxation, hypoglycaemic and diuretic are some of the activities and properties shown by Senna alata plant. Antifungal properties of this plant are considered asimportant and beneficial in medical field. Senna alataconsists of a variety of compounds in different parts of plant in which anthraquinones and aglycones are important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…According to Alonso-Castro et al, 2021 in this review, diarrhoea is a common side effect of many natural products used for self-medication, and it can be caused by a variety of factors. Some herbs, such as aloe vera and senna, have laxative effects that can cause diarrhoea (Ashfaq & Yousaf, 2022). Alotiby et al, 2021 identi ed Stomach pain in this review as a major side effect of herbal medicine use, particularly if the herbs are taken on an empty stomach or in large amounts, a nding corroborated by Tripathi & Bahuguna (2022).…”
Section: Discussionmentioning
confidence: 64%
“…According to Alonso-Castro et al, 2021 in this review, diarrhoea is a common side effect of many natural products used for self-medication, and it can be caused by a variety of factors. Some herbs, such as aloe vera and senna, have laxative effects that can cause diarrhoea (Ashfaq & Yousaf, 2022). Alotiby et al, 2021 identi ed Stomach pain in this review as a major side effect of herbal medicine use, particularly if the herbs are taken on an empty stomach or in large amounts, a nding corroborated by Tripathi & Bahuguna (2022).…”
Section: Discussionmentioning
confidence: 64%
“…Traditional remedies have few negative side effects and do not lead to resistance. C. alata leaves can be used to treat pinworms and fungal infections on the skin, such as tinea versicolor, ringworm, eczema, thrush, and itching [4]. Based on our initial research, the activity of ethanol extracts of C.alata leaves against C. albicans fungi shows that ethanol extracts of C.alata leaves at a concentration of 1.25% produce an inhibition zone of 18.0 ± 0 mm, where the value is greater than the 2% ketoconazole inhibition zone, which is 11.0 ± 0 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been carried out on the efforts of seed germination in various plants of various species, including medicinal plants. Several studies have been reported on the propagation of S. alata [2,8,9].…”
Section: Introductionmentioning
confidence: 99%